2016
DOI: 10.26582/k.48.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Sport education model and self-determination theory

Abstract: Using self-determination theory as a guiding framework, this study analyzed the impact of the Sport Education Model in self-determination and motivation, psychological basic need thwarting, enjoymentsatisfaction, boredom, and intention to be physically active in Physical Education (PE) of secondary school students in Spain. Two groups were selected for the study: an experimental group (EG; n=43), which received 19 volleyball lessons following the Sport Education Model, and a control group (CG; n=43), which rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 49 publications
2
51
0
2
Order By: Relevance
“…Recently, Cuevas et al (2016) confirmed that the intrinsic motivation was significantly higher in the students who experienced the SEM in contrast with the students who participated in the DI, verifying the idea that SEM can produce enjoyment, pleasure, and well-being. These factors can determine the way in which the effort variable increases.…”
Section: Implementation Of Sport Education Model and Its Impact On Thmentioning
confidence: 75%
“…Recently, Cuevas et al (2016) confirmed that the intrinsic motivation was significantly higher in the students who experienced the SEM in contrast with the students who participated in the DI, verifying the idea that SEM can produce enjoyment, pleasure, and well-being. These factors can determine the way in which the effort variable increases.…”
Section: Implementation Of Sport Education Model and Its Impact On Thmentioning
confidence: 75%
“…A possible justification would be supported by students during the SE season having the opportunity to experience a higher level of autonomy in their teaching and learning process, fulfilling one of the main instructional needs demanded by students for the educational stage of high school [35]. In this regard, each group of students had the possibility to create their own warm-up session and to develop the instructional activities at their own pace, which probably led to an increase in students' intrinsic desire to actively participate in PE class [39,42].…”
Section: Discussionmentioning
confidence: 99%
“…Following previous research on SE [36][37][38][39], this study adopted a clustered randomized approach with, a priori, a non-equivalent control group and with pre-intervention and post-intervention measures. Due to each one of the three participating schools having already organized all their high school students into two classrooms, it was impossible to randomize them in accordance with an independent variable (pedagogical models).…”
Section: Design and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations